Pemanfaatan Limbah Elektronik Jenis Optik (Screenprotector Smartphone) Sebagai Filler pada Polyester Matrix Composites - Ridhoni, Fauzan; Ary Wahyudie, Ilham; Masdani, Masdani (Jurnal Inovasi Teknologi Terapan, 2024)
This research aims to test and evaluate the toughness of composite material reinforced with optical type electronic waste (screen protector) with variations in the length and weight of the screen protector pieces as filler. The impact testing method in accordance with the ISO-179 standard is used to determine the toughness of polyester fiber reinforced composite materials. In this research, the composite variation used was a resin and catalyst ratio of 10:2 with variations in the length and weight of the screen protector pieces as filler using variations of the Taguci method. The limitation of this research is that it only focuses on optical type electronic waste reinforced composite materials (screen protectors), and does not involve testing composite materials with other reinforcements. In addition, this research does not discuss the production or construction process of composite materials, but only focuses on testing and evaluating material toughness. Based on the experimental results of this research, it can be concluded that the impact testing results of the 2 process parameters tested, namely waste length, waste weight, with three levels of factors have a great influence on the impact testing of these factors. In order of the most influential factors on the composition of screen protector pieces as filler in composites, namely: length of waste, weight of waste. The most optimal impact test toughness value occurs in the factorial Taguchi L9 design specimen, namely waste length (12.5 cm), waste weight (62 grams). Safety and environmental protection aspects will be considered in this research. The research will be carried out in compliance with relevant safety standards and taking into account possible environmental impacts. This research has a time limit until the end of the research without involving further development or implementation stages. It is hoped that the results of this research will provide a better understanding of the strength and toughness of optical type electronic waste reinforced composite materials (screen protectors) with variations in the length and weight of the screen protector pieces, as well as contribute to the development of better composite materials in the future.